2017
DOI: 10.1016/j.tcr.2017.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Massive bilateral chylothorax post blunt trauma

Abstract: Chylothorax caused by blunt trauma is extremely rare. We present a case of bilateral massive chylothorax post blunt trauma and a review of the literature regarding the identification and management of this rare diagnosis. An eighteen-year-old male was involved in a motor vehicle crash where he sustained multiple injuries including a right, moderate to large, haemopneumothorax, a small left haemopneumothorax, left T8, T9, L1 and L2 acute transverse process fractures and fractures of bilateral 11th ribs. An inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…One patient underwent both thoracotomy and laparotomy. Those patients underwent operation (both thoracotomy and thoracoscopy) had drainage more than 800 cc/days for several days [3,8,9]. Table 1 shows relevant data regarding chylothorax caused by blunt chest trauma.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One patient underwent both thoracotomy and laparotomy. Those patients underwent operation (both thoracotomy and thoracoscopy) had drainage more than 800 cc/days for several days [3,8,9]. Table 1 shows relevant data regarding chylothorax caused by blunt chest trauma.…”
Section: Resultsmentioning
confidence: 99%
“…In the current metadata, conservative treatment succeeded in 71.4% of the cases. [1,4,6,7,9,16,17,[19][20][21][22][23][24]. Routine conservative management is not recommended as it yields 50% mortality rate; this decreased to 10% with classical surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is understandable how an isolated thoracic duct injury can occur following penetrating trauma and there are numerous cases reported in the literature describing this event [10][11][12]. Many cases of thoracic duct injury following blunt force trauma do not happen in isolation, often these cases also involve fractures within the thorax [13][14][15][16][17][18][19][20][21]. These fractures may be associated with direct trauma to the thoracic duct leading to a tear in the lymphatics.…”
Section: Etiology and Demographicsmentioning
confidence: 99%
“…For example, the most common operation performed by MSF is cesarean section [3, 5] and most HIC general surgeons do not learn this procedure during their training. Also, pathologies in HICs may differ: 80% of HIC abdominal trauma is blunt, caused by road traffic accidents, and utilize non‐operative management [6, 7], whereas in the humanitarian setting, traumatic abdominal trauma is usually penetrating, caused by intentional or unintentional injury especially in armed conflict settings, and requires surgery [8, 9]. In a recent publication, Lin and colleagues demonstrated that US general surgery residency did not provide the technical competency to work in humanitarian crises.…”
Section: Introductionmentioning
confidence: 99%